Optimum Dose and Formulation of Centella asiatica L. Urban Extract Against IgG of Wistar Strain Male Mices which Induced by BCG Vaccine - Ermawati, Dian Eka; Sasmito, Ediati; Mufrod, Mufrod; ND., Pramitha Esha; UA., Ni Putu; KD, Anggi; H., Muchammad; S., Aini (Fakultas Farmasi, Universitas Gadjah Mada, 2016)
Objective: Centella asiatica L.Urban contains triterphenoid saphonin, flavonoid, and pectin that believed to have an immunomodulatory effect toward the Immunoglobulin-G in Wistar strain male mices which Induced by BCG vaccine. A study was conducted to find out the optimum dose and formulation of in enhancing on the level of IgG. It’s therefore expected that Cantella asiatica L.Urban can be used as an immunomodulatory suplement in both animals and human.Methods: Centella asiatica L.Urban were macerated with ethanol 50%. This was an experimental study with the post-test control group design. The samples in this study were 35 Wistar strain male mices which divided into 7 groups: negative control [Aquadest 0,5mL/20g BW]; control immunosupresant [Prednison® 0,06mg/20g BW]; control immunostimulant [Levamisol® 0,445mg/20g BW]; ethanolic extract of Cantella asiatica L.Urban with a dose of 50mg; 100mg; 150mg; 200mg/Kg B.W were administered orally fo 10 day, after the treatments implemented, BCG [Bacillus Calmette Guerin] vaccine was infected intraperitoneally on day 10th, 14th, 21st, and 28th. The most effective doses of ethanolic extract of Cantella asiatica L.Urban was further studied for its effect on hormonal assay using ELISA reader which compared with the effects of Prednison® and Levamisol®. Based on simplex lattice design to find the optimum proportion of coefficients a, b, and ab of the equation Y = a (A) + b (B) + ab (A) (B), where A is lactose and B is amylum.Results : Oral administration of ethanolic extract of Cantella asiatica L.Urban at dose of 50mg and 100mg/Kg B.W increased the immunity which showed elevated levels of IgG in the blood serum in Wistar strain male mices that had been induced by BCG vaccine. The optimum formula capsul of Centella asiatica L.Urban extract that use combination of 80% Amylum and 20% Lactose which produce the optimum parameters of disintegration time (≤15minutes) and CV of weight uniformity (≤5%)with the test results had no significant difference to the prediction results of Simplex Lattice Design [p>0.05].Keywords: Centella asiatica L.Urban extract, Immunomodulator, simplex lattice design